A comparative study of fermented buffalo and camel milk with anti-inflammatory, ACE-inhibitory and anti-diabetic properties and release of bio active peptides with molecular interactions: In vitro, in silico and molecular study. (April 2023) - Khakhariya, Ruchita; Sakure, Amar A.; Maurya, Ruchika; Bishnoi, Mahendra; Kondepudi, Kanthi Kiran; Padhi, Srichandan; Rai, Amit Kumar; Liu, Zhenbin; Patil, G.B.; Mankad, Maunil; Hati, Subrota
Abstract: The aim of this study is to compare ACE inhibitory, anti-diabetic and Anti-inflammatory activity of buffalo and camel milk using Lacticaseibacillus paracasei (M11) in combination with yeast Saccharomyces cerevisiae (WBS2A) and to release peptides with antihypertensive and anti-diabetic properties. Fermented buffalo and camel milk were considered for the evaluation of Angiotensin-converting enzyme (ACE) inhibitory and anti-diabetic activities at specific time intervals (12, 24, 36 and 48 h) at 37 °C. For the growth condition optimization, proteolytic activity was evaluated with specific inoculation rates (1.5%, 2.0%, and 2.5%) and at specific incubation periods (12, 24, 36, and 48 h). The highest peptides were produced at 2.5% inoculation rate and at 48 h of incubation in both buffalo and camel milk at 37 °C. Further, camel and buffalo milk fermented with M11+WBS2A significantly lower the overproduction of TNF-α, IL-6, IL-1β and Nitric oxide (NO), that was induced by lipopolysaccharide (LPS) stimulation in RAW 267.4 cells. For protein purification, 2D gel electrophoresis and SDS-PAGE were used. Camel and buffalo milk that had not been fermented displayed protein bands between 10 and 100 kDa and 10 and 75 kDa respectively, whereas all the fermented samples showed bands between 10 and 75 kDa. On SDS-PAGE, in permeates, there were no apparent protein bands. When fermented buffalo and camel milk were electrophoresed in 2D gel, a total of 26 and 25 protein spots were found. In 2D gel electrophoresis, protein spots had sizes between 10 and 37 kDa. In RP-HPLC, water-soluble extracts (WSEs) of ultra-filtered fractions were used to distinguish different fractions of a peptide. Peakview software was used to characterize the LC/MS results. Fourier transform-infrared spectroscopy (FTIR) was used to evaluate various functional groups of fermented milks. In molecular docking study, the peptide sequences identified from the fermented buffalo milk (FBM) and camel milk (FCM) were examined for their binding affinity against the binding sites of hPAM and hMGA. Graphical abstract: Image 1 Highlights: Traditionally, Buffalo and camel milk shows the biofunctional attributes since long time. Fermented Buffalo and camel milks contain physiologically Bioactive peptides Buffalo and Camel milk fermented with Lacticaseibacillus paracasei (M11) in combination with S. cerevisiae (WBS2A) also act as probiotics products with antidiabetic, ACE inhibitory and anti-inflammatory activities Promising anti-inflammatory activity of fermented Buffalo and camel milks were observed in RAW 264.7 macrophage cell Antidiabetic peptides were identified from fermented Buffalo and camel milks DMPIQAFLLYQEPVLGPVR and FFIFTCLLAVVLAK from buffalo and camel fermented milk matched with antihypertensive and antidiabetic property respectively.